EXPERIENTIAL FUNCTION IN JOKO WIDODO’S SPEECH AT APEC CEO SUMMIT 2014 IN BEIJING, CHINA - Maragoti Maragoti; Amrin Saragih; Sri Minda Murni (LINGUISTIK TERAPAN, 2018)
This study presents a research conducted on Experiential Function in Joko Widodo’s speech at APEC Summit 2014 in Beijing, China. The main objective was to describe the types and the dominant processes and Circumstances in Experiential Function in Joko Widodo’s speech at APEC Summit 2014 in Beijing, China. It presented a qualitative design dealing with quantifiable (numeric) mode. The source of data was taken from Experiential Function in Joko Widodo’s speech at APEC Summit 2014 in Beijing, China. The data were collected by applying documentary technique. The data analysis found out the findings indicating that there were 6 types of process used, they were 21 (22.11 %) Material Process, 39 (41.06 %) Mental Process, 28 (29.47 %) Relational Process, 0 (0.%) for Behavioral Process, 6 (6.36 %) Verbal Process, and 0 (0. %) Existential Process. It means that the dominant pattern of Process is Mental. Meanwhile, there are 7 patterns of Circumstances found in the Joko Widodo’s speech at APEC Summit 2014 in Beijing, China They are 0 (0 %) for Extent, 31 (32.63%) for Location, 13 (13.68%) for Manner, 5 (5.26%) for Cause, 5 (5.26 %) for Contingency, 0 (0 %) for Accompaniment, and 0 (0 %) for Role. It means that the dominant pattern of Circumstance is Location. It proves that the use of Process and Circumstance were related to the context of situation.Keywords: Experiantial Function, Jokowi’s speech, Process.